The clinical toxicology laboratory : contemporary practice of poisoning evaluation - Kwong, Tai C. ;Magnani, Barbarajean ;Rosano, Thomas G. ;Shaw, Leslie M. (Washington, DC : American Association for Clinical Chemistry, 2013)
This is an updated edition of the unique and successful textbook on laboratory evaluation of the poisoned patient. An outstanding group of experts in the fields of laboratory medicine, emergency medicine, and toxicology who herald from poison control centers and academic, governmental, and private laboratories has helped produce this new edition. The wide range of disciplines represented points to the very essence of the contemporary practice of toxicology: the dramatic advances in the care of the poisoned patient, the advent of regional poison centers, and the successful efforts of clinical laboratories to adapt new and effective technologies to support changing diagnostic and treatment modalities. Major topics include: the epidemiology of poisoning and substance abuse, including abuse of prescription drugs; pharmacokinetic and toxicokinetic behavior of the most prevalent drugs of abuse, medications, and environmental poisons; clinical manifestations of poisons and approaches to diagnoses; critical appraisal of laboratory and point-of-care testing methods, sample types, and tests for sample adulteration; laboratory support of opioid therapy for chronic noncancer pain; biological monitoring of chemical exposures; pharmacogenetic principles and toxicity risk assessment; principles and applications of advanced analytical techniques; and an assessment of the provision of a clinical toxicology laboratory service that is based on examining clinical needs, technology requirements, and financial justifications. This textbook should be of interest to clinical chemists; clinical pathologists; clinical laboratory directors, managers, supervisors, and technologists; pharmacists; poison control center specialists; and students, residents, and fellows. They will find valuable, state-of-the-art information in this book that will assist them in their practice and teaching of toxicology in the current clinical laboratory environment.
Includes bibliographical references and index.
Keywords: TOXICOLOGY